An Investigation into the Performance and Problems of the Elevator System at PPR Sinar Intan Residential - BIN ABD RAHMAN, MUHAMMAD AFIQ AKMAL; Mohd Fahmi Bin Abdul Rahman (Progress in Engineering Application and Technology, 2025)
This study evaluated the performance and problems associated with the elevator system at PPR Sinar Intan Residential, emphasizing the need for efficient vertical transportation in multi-story buildings. The research investigated issues such as frequent breakdowns, misuse, and damage, particularly by children, while examining compliance with Jabatan Kerja Raya (JKR) specifications. Employing a mixed-methods approach, the study incorporated questionnaire, interviews, and field measurements to assess the system’s current performance and user satisfaction. Findings revealed that average waiting times exceeded 15 minutes, and malfunctions occurred approximately 30% of the time during peak usage hours. Additionally, user satisfaction ratings dropped to 60%, indicating significant dissatisfaction with the current elevator service. Proposed improvements included enhanced maintenance schedules, preventive measures to minimize misuse, and the addition of elevators to reduce congestion. Addressing these concerns is crucial for ensuring safety, operational efficiency, and improved mobility within the residential community. This research provided actionable insights for optimizing elevator performance and fostering a safer, more reliable environment for residents.